Dielectric polymer nanocomposites: Past advances and future prospects in electrical insulation perspective. (6th September 2021) - Pandey, Jeewan Chandra; Singh, Manohar
Abstract: Polymeric materials enjoy widespread acceptance among electrical insulation design engineers due to their multi‐functional attributes (e.g., excellent dielectric properties, high strength to weight ratio, and ease of molding). However, charge accumulation at the high DC field, poor discharge resistance, low thermal conductivity, limited‐service temperature range, and inadequate stiffness have proven to be severe obstructions to far‐reaching utilization of these materials. To ensure the reliability of today's electrical power systems, novel dielectric materials with enhanced functionalities are essential. An idea that originated under the name of polymer nanocomposites (PNCs) is supposed to provide a viable solution to the challenges mentioned earlier. PNCs are made by mixing a small quantity of nanometer‐sized fillers into a polymer matrix and dispersing them uniformly. To effectively use PNCs in electrical insulation for power apparatus, extensive research into the physical and chemical phenomena associated with these new materials is required. This article aims to provide a comprehensive review of previous research on dielectric PNCs, including synthesis, electrical and nonelectrical characterization, and attendant issues from an electrical insulation standpoint. Abstract : Synthesis and characterizations of dielectric polymer nanocomposites: Past advances and future prospects in electrical insulation perspective.